THE ROLE OF BRAND LOVE AS MEDIATION FACTOR TOWARD CUSTOMER LOYALTY - Yusniar Yusniar; Jasman J Ma'ruf; Sulaiman Sulaiman; Permana Honeyta Lubis (Aceh International Journal of Social Science, 2015)
The purpose of this research is to explain the effect either directly or indirectly directly from the brand love mediation variables on the relationship of brand trust variables consisting of Brand Excellence, Brand Strength and Brand Uniqueness on Brand Loyalty to Car customers in Aceh. Method data collection used is to spread the questionnaire to as many as 400 respondents, with sampling technique that is Purposive Random Sampling Based on result of data analysis, hence can be concluded that variable of brand image proved to have partially and simultaneous, positive and significant influence to brand love. This condition means that the better image of mrek will affect the increasing of brand love to car customers in Aceh. Keywords: Brand Image, Brand Love, Brand loyalty